Reverse–normal immunopurification: An effective approach for purifying recombinant erythropoietin from its analogues in doping analysis - Sen He; Die Wu; Chengshuai Niu; Xinchao Liu; Jie Zhang; Liangzhi Xie; Laurent Martin; Kaifeng Liu; Xinmiao Zhou; Lisi Zhang (Journal of Sport and Health Science, 2025)
Background: Recombinant erythropoietin (rEPO) is commonly used in therapy but may be abused in sports to enhance endurance. In doping analysis, rEPO can be detected in human urine or blood samples at picogram (pg) levels based on its slightly higher molecular weight (MW) than that of endogenous EPO using western blotting (WB). However, a type of variant erythropoietin (VAR-EPO) encoded by the EPO c.577del variant has a similar MW to rEPO, and these 2 molecules cannot be distinguished using conventional analytical methods. A fit-for-purpose method needs to be developed immediately. Methods: In this study, we introduced a reverse–normal immunopurification technique for sample pretreatment to remove VAR-EPO from samples to eliminate its interference with rEPO detection. Firstly, a rabbit monoclonal antibody (mAb) that can specifically recognize trace amounts of VAR-EPO with high affinity was generated. Then, using this antibody to enrich VAR-EPO, we developed reverse–normal immunopurification coupled with WB on the purpose of analyzing rEPO in urine and serum samples. Next, the method was fully validated and evaluated using blank samples, spiked samples and rEPO excreted samples. Finally, the identification criteria of rEPO was established. Results: A specific anti-VAR mAb with high affinity was developed. Using it, we developed the doping analytical method for rEPO. Our method effectively detects and removes VAR-EPO, enabling accurate rEPO detection. Conclusion: A method has already been applied for rEPO confirmation in routine doping analyses.